Bank 3.0 : Why Banking Is No Longer Somewhere You Go But Something You Do. - King, Brett (New York : Wiley, 2012)
The first edition of BANK 2.0 took the financial services world by storm and became synonymous with disruptive customer behaviour, technology shift and new banking models. In BANK 3.0, Brett King looks at the latest trends that are redefining financial services and payments. From the global scramble for dominance of the mobile wallet, the expectations created by tablet computing, the operationalizing of the cloud and the explosion of social media he explores: How Social Media has exposed pricing, over-regulation, outdated processes and poor policy, How mobile technology is com.
Screen (Web/Tablet/Mobile) firstCross-sell to existing customers; Combating banner blindness; Internet channel improvement today; Key lessons; Chapter 6: Mobile Banking-Already Huge and It's Just Getting Started; The greatest device ever sold; Mobile's ability to shift banking; The landscape; Mobile banking delivery versus payments; Mobile in Commerce; Bringing banking to the unbanked; The mobile as a bank account; What does the future hold?; Beyond the App Store; Key lessons; Chapter 7: The Evolution of Self-Service; Self-service banking-where it all started; The drive for efficiency.
Are ATMs more than just cash dispensers?
Print version record.
Keywords: Banks and banking; BUSINESS & ECONOMICS -- Banks & Banking; Banks and banking; Electronic books